(untitled) (Global Media Journal - German Edition, 2016)
In the actual debate on refugees in Germany the media’s role was heavily disputed. To understand this controversy, this study examines hostile media perceptions from the audience perspective. Building up on previous research on the hostile media phenomenon and considering literature on pro- and anti-immigrant attitudes, this study explores the effect of positive and negative attitudes towards refugees as well as of mainstream media, social media and interpersonal com munication on hostile media perceptions. Using survey data (N=1005) and applying structural equation modelling, several hypotheses on the effects of attitudes and communication variables were tested. The results demonstrate that perceptions of media bias are strongly influenced by people’s negative and positive attitudes towards refugees and the basic hostile media hypothesis was confirmed. Moreover, our findings reveal that the perceived intensity of media coverage on contested aspects of the refugee issue also has an effect on perceptions of hostility. However, the various communication variables did not prove to have direct effects, whereas mainstream media use, social media use, and interpersonal communication with refugees had indirect effects on the hostile media perception.